2019
DOI: 10.1111/aos.14166
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of atropine 0.01% for the treatment of childhood myopia in European patients

Abstract: Purpose: To evaluate the efficacy and safety of atropine 0.01% in slowing myopia progression in European paediatric patients. Methods: Retrospective, medical records review study. Medical charts of paediatric patients with a myopia progression > 0.5 D/year treated with atropine 0.01% for at least 1 year were included. Patients receive a complete ophthalmic examination before and 12 months after initiation of atropine treatment. A group of myopic untreated children serves as a control group. The rate of myopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 31 publications
7
50
2
1
Order By: Relevance
“…Our study recorded a -0.55D progression of myopia after atropine 0.01% treatment for 1 year, which is similar to the -0.54D progression reported by Sacchi et al in 2019 ( Sacchi et al, 2019 ), the -0.64D progression reported in the LAMP study ( Yam et al, 2019b ), and the -0.43D progression reported in the ATOM2 study ( Chia et al, 2012 ). In the present study, the mean changes in axial length at 1 year from baseline was 0.43 ± 0.52 mm.…”
Section: Discussionsupporting
confidence: 90%
“…Our study recorded a -0.55D progression of myopia after atropine 0.01% treatment for 1 year, which is similar to the -0.54D progression reported by Sacchi et al in 2019 ( Sacchi et al, 2019 ), the -0.64D progression reported in the LAMP study ( Yam et al, 2019b ), and the -0.43D progression reported in the ATOM2 study ( Chia et al, 2012 ). In the present study, the mean changes in axial length at 1 year from baseline was 0.43 ± 0.52 mm.…”
Section: Discussionsupporting
confidence: 90%
“…However, not all children that observed pupil dilation also experienced photophobia. We observed a low rate of photophobia of 5.6%, comparable to Wei et al [32], and even slightly lower than what Sacchi et al [38] reported in their retrospective analysis. There was no need to prescribe photochromatic or multifocal glasses.…”
Section: Adverse Side Effectssupporting
confidence: 83%
“…Joachimsen et al observed a pupil dilation of 1 mm in children with 0.01% atropine therapy and negligible hypoaccomodation without an effect on near vision [ 17 ]. Sacchi et al reported photophobia in 9.6% as only detectable adverse event with 0.01% atropine, and data on pupil size were not presented [ 20 ]. Diaz-Llopis and Pinazo-Durán reported that in a 5-year observation period 2% of children treated with 0.01% atropine discontinued therapy due to photophobia, difficulties in reading, mydriasis or headache [ 21 ].…”
Section: Discussionmentioning
confidence: 99%